Theater as a pedagogical element, from a human rights perspective: towards a concept of peacebuilding – case study- (2022)
This paper presents the results of the investigation titled The theater as a pedagogical element, from a Human Rights perspective: Towards a concept of peacebuilding - Case studies. Made by Juan Daniel Ocoró Obregón, Bachelor of Performing Arts, to opt for the title of Master in Human Rights and Culture of Peace, from the Pontificia Universidad Javeriana-Cali. In it, a brief summary of the relationship between theater and Human Rights is presented as to how they help to build peace. In the same way, it delves into the case study of two plays that promote the culture of peace in their speech. Finally, it shows how from the theories on collective creation, social theater, community theater, forum theater, and legislative theater, the workshop "Theater and construction of peace" is built, which is put into practice with young people. of the ICBF and gives rise to the design of the diploma in Human Rights and Peacebuilding, to accompany the young leaders of the social outbreak in the Department of Valle del Cauca in a teaching-learning process.